Adapting Indonesia’s Tax Incentive Strategy In The Post Pillar Two Era - Johanes Glorinus Saragih (Journal of Tax Policy, Economics, and Accounting (TAXPEDIA), 2023)
Indonesia, as a developing country striving for economic growth and technological advancement, faces the imperative challenge of re-evaluating its tax incentive regime in light of the global tax landscape's recent transformation through BEPS Action 1 Pillar Two. Using qualitative research methodology, this study delves into the framework of Pillar Two and its implications for Indonesia's tax incentives policy. This paper highlights the pressing need for Indonesia to recalibrate its tax incentive strategy and proposes that Research and Development (R&D) tax incentives as a promising solution, specifically focusing on input R&D activities that are compliant with The Global Anti-Base Erosion (GloBE) rules. This study examines the potential of R&D tax incentives to stimulate innovation, attract foreign investments, and ultimately contribute to long-term economic growth. As Indonesia charts its path toward economic prosperity, rethinking its tax incentive policy is paramount.